Peripheral Blood Biomarkers for Early Diagnosis, Severity, and Prognosis of Checkpoint Inhibitor-Related Pneumonitis in Patients With Lung Cancer - Lin, Xinqing; Deng, Haiyi; Yang, Yilin; Wu, Jianhui; Qiu, Guihuan; Li, Suyang; Xie, Xiaohong; Liu, Ming; Xie, Zhanhong; Qin, Yinyin; Song, Yong; Zhou, Chengzhi (Frontiers in Oncology, 2021)
Background: Checkpoint inhibitor-related pneumonitis (CIP) is a potentially fatal, immune-related adverse event that occurs during treatment with immune checkpoint inhibitors (ICIs). However, the roles played by peripheral blood parameters in CIP development remain unclear. Here, we aimed to identify which blood biomarkers correlated with the development and prognosis of CIP in patients with lung cancer. Methods: We conducted a retrospective analysis of 87 patients with CIP (CIP group) and 87 patients without CIP (control group). We compared the baseline values and changes in various blood parameters between the CIP and control groups. The CIP outcomes were collected and compared according to the median values of these parameters. Results: Squamous carcinoma (odds ratio: 3.02; p = 0.004) and ICI monotherapy (odds ratio: 6.56; p = 0.004) correlated with CIP occurrence. In the CIP group, interleukin (IL)-6 and platelet-to-lymphocyte ratio (PLR) at CIP were significantly increased relative to baseline. By contrast, IL-6 and PLR reduced over time in the control group. Significant decrease in absolute lymphocyte count (ALC) and increases in IL-10, neutrophil to lymphocyte ratio (NLR), and lactate dehydrogenase (LDH) levels were observed from baseline to CIP. No significant change in any parameters was observed in the control group relative to baseline. Albumin (ALB) decreased in both groups, but the decrease in the CIP group was greater (9.21% vs. 2.44%; p = 0.020). High IL-6, NLR, and PLR levels, and low levels of ALC and ALB measured at the time of CIP symptom onset were associated with severe pneumonitis. The CIP grade (hazard ratios [HR], 0.11), IL-6 (HR, 0.07), ALC (HR, 0.42), NLR (HR, 0.33), and albumin (HR, 0.32) levels were correlated with overall survival in CIP. Conclusions: Increase in IL-6, IL-10, NLR, PLR, and LDH levels or reduced ALC and ALB levels were associated with CIP. High-grade CIP, high levels of IL-6 and NLR, or low levels of ALC and ALB were correlated with poor CIP prognosis.